Structural Coupling System for Cognitive Modeling in Immersive VR Assessment Tasks - Sekiguchi, Takuro; Obo, Takenori; Matsuda, Tadamitsu; Kubota, Naoyuki (Journal of advanced computational intelligence and intelligent informatics, 2024)
Unilateral spatial neglect (USN) is a disorder characterized by the inability to attend to the space opposite the cerebral hemisphere lesion, significantly hindering daily activities. Due to the complex neural circuitry of the brain, understanding the mechanisms of USN has proven challenging. In clinical settings, the Behavioral Inattention Test (BIT), a paper-based examination, is commonly used to assess USN. However, improved scores on this test do not necessarily guarantee functional improvement, as it solely evaluates performance in a two-dimensional space. To address this limitation, various approaches utilizing information and communication technology (ICT) and measurement devices in rehabilitation engineering have been proposed. However, related studies have focused on analyzing motor responses to specific sensory stimuli, and the assessment measures often fail to capture a patient’s symptoms in dynamic environments. Therefore, this study proposes a methodology for modeling human spatial cognition. This cognitive architecture utilizes a structural coupling system that integrates parameters from multiple computational intelligence subsystems. In this study, we constructed a simulation environment capable of replicating the movements of patients with USN using empirical data collected from actual experiments. Furthermore, in this simulation environment, we developed patient agents that incorporated the proposed cognitive architecture. The experimental results suggest that hypothesis testing concerning attention mechanisms can be applied through the performance of patient agents within the simulation environment.